Vocal Hoarseness and a Subglottic Mass - Sassan Rafizadeh PhD; Ken Yoneda MD; Amir A. Zeki MD (SAGE Publishing, 2015)
We report a patient with tracheopathia osteoplastica (TPO), a rare or perhaps underrecognized disorder, detected in approximately 1 in every 2000 to 5000 patients who undergo bronchoscopy. TPO is marked by proliferation of bony and cartilaginous spurs leading to airway stenosis. Multiple submucosal cartilaginous and osseous nodules can develop in the respiratory tract and may involve the entire trachea and mainstem bronchi. Symptoms may range from a completely silent condition to life-threatening respiratory failure and diagnosis is made based on radiological and bronchoscopic findings. Although the etiology has not been established, TPO can be familial and is sometimes associated with chronic inflammation, such as seen with rheumatic diseases. This case highlights the need for understanding TPO so that it can be differentiated from potentially serious conditions such as necrotizing granulomatous diseases, invasive infections, and cancer.